TINGKAT HUNIAN ANOA DATARAN RENDAH (Bubalus depressicornis) DI SUAKA MARGASATWA NANTU - Fahrul Ramadhan Azdin; Hard Napoleon Pollo; Reynold P Kainde (COCOS, 2022)
Abstract Anoa is endemic species that can only be found on the islands of Sulawesi and Buton. Currently the anoa population is decreasing due to habitat destruction and hunting for meat. This study aims to estimate the occupancy rate and analyze the distribution pattern of the lowland anoa in Nantu Wildlife Reserve. This research used an occupancy survey method using camera traps. Camera traps are placed in locations with high likelihood of obtaining images of animals, such as near streams, ridges and animal tracks. The camera trap is mounted on a tree trunk with a height of 60 cm above ground level. The results of the research show that the lowland anoa inhabits about 58,3% of the area of Nantu Wildlife Reserve. Keywords : Occupancy, Camera Trap, Lowland Anoa, Nantu Wildlife Reserve.